Paradoxes in Göttingen - Peckhaus, Volker (One Hundred Years of Russell's Paradox. Mathematics, Logic, Philosophy)

Garantiert Widerspruchsfreiheit Existenz? - Peckhaus, Volker (Was folgt? Themen zu Wessel)

Calculus Ratiocinator vs. Characteristica Universalis? The Two Traditions in Logic, Revisted - Peckhaus, Volker (History and Philosophy of Logic (Special Issue in Honor of Ivor Grattan-Guinness, hg. v. John W. Dawson, Jr.))
Rezension: Zbl. Math. 1100.03006; MR 2055237 (2005:03004; J.W. Dauben).

Dignaga’s Logic of Invention - Peckhaus, Volker (History of the Mathematical Sciences)
Rezension: Zbl. Math. 1049.01008 (A. C. Lewis).

Schröder’s Logic - Peckhaus, Volker (Handbook of the History of Logic, Bd. 3: The Rise of Modern Logic: From Leibniz to Frege)

Scholz als Metaphysiker - Peckhaus, Volker (Heinrich Scholz: Logiker, Philosoph, Theologe)

Who was Wilhelm Schlötel? - Peckhaus, Volker (Filosofisia tutkielmia - Philosophical Studies in honorem Leila Haaparanta)

Novel Modulation Schemes for Conventional and Sparse Matrix Converters Facilitating Reactive Power Transfer Independent of Active Power Flow - Schafmeister, Frank; Kolar, Johann (Proc. 35th IEEE Power Electronics Specialists Conference (PESC))

Enhanced Control Scheme for Three-Phase / Three-Level Rectifiers at Partial Load - Ide, Peter; Schafmeister, Frank; Fröhleke, Norbert; Grotstollen, Horst (Proc. 35th IEEE Power Electronics Specialists Conference (PESC))

Novel Hybrid Modulation Schemes Extending the Reactive Power Control Range of Conventional and Sparse Matrix Converters Operating at Maximum Output Voltage - Schafmeister, Frank; Kolar, Johann (Proc. 11th International Power Electronics and Motion Control Conference (EPE-PEMC))

Active Suppression of Torsional Oscillations - Böcker, Joachim; Amann, Notker; Schulz, Bernd (IFAC Proceedings Volumes)
Keywords: General Medicine

Active Damping of Drive Train Oscillations for an Electrically Driven Vehicle - Amann, Notker; Böcker, Joachim; Prenner, Franz (IEEE/ASME Transactions on Mechatronics)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Tolerance band controller for a three-level four-quadrant converter including DC link balancing - Böcker, Joachim (2004 IEEE 35th Annual Power Electronics Specialists Conference (IEEE Cat. No.04CH37551))

Derivation of integrated magnetic components using reluctance and mathematical modeling - Njiende, H.D.; Fröhleke, N.; Böcker, Joachim (2004 IEEE 35th Annual Power Electronics Specialists Conference (IEEE Cat. No.04CH37551))

Inverter topologies for ultrasonic piezoelectric transducers with high mechanical Q-factor - Kauczor, C.; Fröhleke, Norbert (2004 IEEE 35th Annual Power Electronics Specialists Conference (IEEE Cat. No.04CH37551))

Low Voltage Asymmetrical Half-Bridge Converter with Integrated Magnetics - Wetzel, H.; Siegel, A.; Njiende, H.; Fröhleke, Norbert; Böcker, Joachim (11th International Power Electronics and Motion Control Conferences, Riga, Latvia)

Modelling of Influences to a Linear-Drive-System - Schulz, B.; Pottharst, A.; Fröhleke, N.; Böcker, Joachim (11th International Power Electronics and Motion Control Conferences, Riga, Latvia)

Operating Point Assignment of a Linear Motor Driven Vehicle Using Multiobjective Optimization Methods - Pottharst, A.; Baptist, K.; Schütze, O.; Böcker, Joachim; Fröhleke, N.; Dellnitz, M. (11th International Power Electronics and Motion Control Conferences, Riga, Latvia)

Energy Storage Scheme for Rail-guided Shuttle using Ultracapacitor and Battery - Li, R.; Pottharst, A.; Fröhleke, N.; Böcker, Joachim (11th International Power Electronics and Motion Control Conferences, Riga, Latvia)

Analysis and Design of Improved Isolated Full-Bridge Bi-Directional DC-DC Converter - Li, R.; Pottharst, A.; Fröhleke, N.; Böcker, Joachim (PESC 2004, Aachen, Germany)